Common and unique neuro-functional basis of induction, visualization, and spatial relationships as cognitive components of fluid intelligence. - Ebisch, S; Perrucci, MG; Mercuri, P; Romanelli, R; Mantini, D; Romani, G; Colom, R; Saggino, A (2012)
Neuroimaging research of fluid intelligence (Gf) has mainly focused on the neural basis of abilities explaining performance on cognitive tasks. However, the neuro-functional basis of clearly defined theoretical cognitive components underlying Gf remains unclear. Induction, visualization, and spatial relationships have the highest relevance for Gf (Carroll, 1993). Here we report a functional magnetic resonance imaging (fMRI) study exploring the neural correlates of these abilities characterized by their unidimensionality and matched for task-difficulty, as evidenced by a psychometric calibration study. Twenty-two healthy young adult females, recruited from a large sample of 300 participants, with either below- or above-average Gf abilities underwent fMRI scanning during Gf task performance. The results reveal that these tasks activate a shared frontoparietal network. Specific activations were also observed, in particular for induction and visualization. The key findings suggest that Gf comprises distinguishable cognitive abilities, but the Gf construct is associated with a common network.